2022
DOI: 10.1155/2022/9935192
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Cognitive Impairment Research Progress on Application of Brain-Computer Interface

Abstract: Brain-computer interfaces (BCIs), a new type of rehabilitation technology, pick up nerve cell signals, identify and classify their activities, and convert them into computer-recognized instructions. This technique has been widely used in the rehabilitation of stroke patients in recent years and appears to promote motor function recovery after stroke. At present, the application of BCI in poststroke cognitive impairment is increasing, which is a common complication that also affects the rehabilitation process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 119 publications
0
1
0
Order By: Relevance
“…BCI shows promise in the future of treating VD patients, specifically those who suffered from a stroke [125]. BCI technology can assist care providers to objectively assess the cognitive function of patients as well as cognitive function of patients suffering from VD [125].…”
Section: Brain Computer Interface (Bci)mentioning
confidence: 99%
See 1 more Smart Citation
“…BCI shows promise in the future of treating VD patients, specifically those who suffered from a stroke [125]. BCI technology can assist care providers to objectively assess the cognitive function of patients as well as cognitive function of patients suffering from VD [125].…”
Section: Brain Computer Interface (Bci)mentioning
confidence: 99%
“…BCI shows promise in the future of treating VD patients, specifically those who suffered from a stroke [125]. BCI technology can assist care providers to objectively assess the cognitive function of patients as well as cognitive function of patients suffering from VD [125]. One study of 14 basilar artery stroke patients showed sensorimotor rhythm neurofeedback training(SMR-NF) with BCI systems used positively affected memory functioning versus 14 patients that did not have BCI feedback [126].…”
Section: Brain Computer Interface (Bci)mentioning
confidence: 99%
“…Studies have shown that more than 60% of stroke patients have cognitive dysfunction and up to 33% may progress to dementia; thus, early intervention is considered essential. [1][2][3] In real-world clinical practice, however, the management of stroke patients mainly focuses on physical symptoms, while cognitive decline is likely to be ignored. The Xingnao Kaiqiao acupuncture technique, pioneered by Academician Shi Xuemin, chooses acupoints that have the effects of activating the brain, regulating visceral function, and dredging meridians, so as to improve patient cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the effectiveness of applying BCI using mental practice in motor recovery for subacute and chronic stroke patients with hemiparesis (6,(11)(12)(13)(14)(15)(16)(17)(18)(19). Furthermore, a relevant rehabilitation study combing BCI and mental practice showed promising results for the recovery of cognitive skills (executive functions, language, memory, attention, and visuospatial skills) in post-stroke patients (20).…”
Section: Introductionmentioning
confidence: 99%